Microelectronic sensors for measurement of electromagnetic fields of living cells and experimental results - Jelínek, F; Pokorný, J; Saroch, J; Trkal, V; Hasek, J; Palán, B (Bioelectrochemistry and bioenergetics (Lausanne, Switzerland), 1999)
Microelectronic sensors are used for measurements of electromagnetic fields generated by synchronized cultures of yeast cells. Cold sensitive mutant tub2-401 of Saccharomyces cerevisiae is used. The measured electromagnetic signals in the frequency range from 8 to 9 MHz are compared with evolution of the reassembled microtubules. The detected signals peak in the time interval 25-30 min and 45-60 min after the release of the cells from the restrictive to the permissive temperature. The first maximum corresponds to the stage when the mitotic spindle is formed and binds chromatids. The second maximum is measured when the processes of anaphase A and of anaphase B take place.
Keywords: mikrotubuly; Saccharomyces cerevisiae; mikroelektrody; Microtubules; biosenzitivní techniky; Biosensing Techniques; Electromagnetic Fields; Microelectrodes; elektromagnetická pole